A Study on overall Impact of Displacement on Society in India - Pare, Ankur (Universal Research Reports, 2019)
Large dams, a tool for development in the past century, have changed the lives of millions, altered nations and had widespread environmental, economic and social effects. With the increasing amount of data available, the effects of dams can be assessed with greater accuracy and validity. Development-induced displacements now exceed those resulting from conflict situations and natural disasters. The displaced population usually suffers various forms of impoverishment including homelessness and social disarticulation. This study seeks to contribute to strategies for mitigating these negative impacts by improving resettlement policies. The problems of resettlement and rehabilitation are emphasized in the article as are further displacement effects due to this process. The inequality between development beneficiaries and those who must bear the majority of the development costs is also addressed.